2019
DOI: 10.18415/ijmmu.v5i5.535
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy Adherence Level and Associated Factors Among HIV/AIDS Patients in Jimma Zone Government Health Facilities, ART Clinics, South-west Ethiopia

Abstract: Optimal and strict adherence to Antiretroviral Viral Therapy a need for over the long period to achieve the goals of ART and obtain maximum benefits of ART. However, PLWHA find it very difficult to take ARVs drug as precisely as they should for a number of reasons. Therefore, this study aimed at examining the level of antiretroviral therapy adherence and identifying possible associated factors for ART adherence behavior in Jimma zone government ART facilities. A facility based cross-sectional study was  conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…In this study, the magnitude of adherence to antiretroviral therapy was reported to be 74.63% (95% CI: 71.277.3%). This is in line with studies done in Western Ethiopia, 7 Southwest Ethiopia, 6,9 Southern Ethiopia, 10 Northeastern Ethiopia, 11 Western Africa, 12 and Sub-Saharan Africa, 13 which reported 73.1%, 75.7%, 73.6%, 77.1%, 71.8%, 73%, and 72.9% respectively.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the magnitude of adherence to antiretroviral therapy was reported to be 74.63% (95% CI: 71.277.3%). This is in line with studies done in Western Ethiopia, 7 Southwest Ethiopia, 6,9 Southern Ethiopia, 10 Northeastern Ethiopia, 11 Western Africa, 12 and Sub-Saharan Africa, 13 which reported 73.1%, 75.7%, 73.6%, 77.1%, 71.8%, 73%, and 72.9% respectively.…”
Section: Discussionsupporting
confidence: 90%
“…This might be because easy accessibility of services including medication will improve utilization. 19 People with easy access to HAART and other important medications may adhere to prescribed medication compared with those who lack access. Substance users were also shown to be more likely to have poor adherence in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20] Previous studies also showed that proximity to the healthcare facility, the availability of HAART drugs, and the patients' satisfaction with health service delivery were found to be significantly associated with HAART adherence. 19,[21][22][23] Despite the above reports, limited studies were conducted after the initiation of the "test and treat" strategy in August 2016 24 and the first-line HAART regimen change in the study area. Therefore, this study assessed the level of adherence to HAART among people living with HIV in Eastern Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests optimal and strict adherence of 95% and above is required over the long term to ensure the full benefits of the treatment [ 12 ]. Large-scale surveys have buttress reports that show high levels of positive outcomes of ARVs adherence should range between 80%-95% depending on the varying levels of ARV potency [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to ART among people living with HIV/AIDS (PLWHA) is multifaceted and requires; a proper understanding of ART and HIV, conscious efforts to comply with adherence counselling, education, changing lifestyle, proper nutrition, presence of psychosocial support, active supportive care and availability of a considerate home caregiver [ 12 ]. Implying an interrelated coordinated effort involving PLWHA, their home caregivers and formal health caregivers is considered crucial [ 17 ].…”
Section: Introductionmentioning
confidence: 99%